GoArt Database - Norrback, Johan; Göteborg Organ Art Center, University of Gothenburg (University of Gothenburg, 2012)
GOArt (Göteborg Organ Art Center) is a research center that specializes in integrated studies of instruments and performance. The pipe organ and its related keyboard instruments - the clavichord, harpsichord, harmonium, and fortepiano - form the research field. The organ database system was developed 1995 - 2000. The main goal was to create a database structure in which it is possible to store both technical and historical information on organs. In addition to storing information on organs, it was important to be able to store information on archive documents and persons related to the instruments. The database thus consists of four main parts, divided into: technical information about the organs, historical information, other archival data, and information about persons linked to the organs. This structure makes it possible to select a certain point of time in history and to trace the historical process, in the database stored as a network between organs, documents, and persons. The user can navigate backwards or forwards in time and will always be informed about connections between organs, documents, and persons at every point in this historical network.
The purpose of the database has been to serve as a documentation tool for results from research as well as a tool for analysis and evaluation. The database is also a source of information for future research projects.
There are at present more than 200 historical Swedish organs, 870 archive documents and 1900 person records in the database.

Purpose:

The purpose of the database has been to serve as a documentation tool for results from research as well as a tool for analysis and evaluation. The collection of data to the database helps to preserve a unique Swedish cultural heritage for posterity, thus supporting sustainable development. The database information may help curators to make decisions with financial implications, as it may provide a basis for assessing the need and value of measures. The database will also contribute to the documentation and inventory of parts of organs that are unique and protected by the Antiquities Act.

GOArt (Göteborg Organ Art Center) är ett forskningscentrum som specialiserat sig på integrerade studier av instrument och utförande. Orgeln och dess relaterade klaviaturinstrument - klavikord, cembalo, tramporgel och hammarklaver - bildar forskningsområdet. Orgeldatabassystemet utvecklades 1995 - 2000. Huvudsyftet var att skapa en databas i vilken det är möjligt att lagra både teknisk och historisk information om orglarna. Utöver information om själva orgeln var det viktigt att kunna lagra information om arkivhandlingar och personer med anknytning till instrumenten. Databasen innehåller således fyra huvuddelar som materialet delas upp i: teknisk information om orglarna, historisk information, andra arkivdata, samt information om personer knutna till orglarna. Denna struktur gör det möjligt att välja en viss tidpunkt i historien och att spåra den historiska processen, i databasen lagrad som ett nätverk mellan orgel, dokument och personer. Användaren kan navigera bakåt eller framåt i tiden och kommer alltid att informeras om kopplingar mellan orgel, dokument och personer i varje punkt i detta historiska nätverk.
Syftet med databasen har varit att fungera som dokumentationshjälpmedel för resultat från forskning samt ett verktyg för analys och utvärdering. Databasen är också en källa till information för framtida forskningsprojekt. Det finns för närvarande mer än 200 historiska svenska orglar, 870 arkivdokument och 1900 personposter i databasen.

Syfte:

Syftet med databasen har varit att fungera som ett dokumentationshjälpmedel för resultat från forskning samt ett verktyg för analys och utvärdering. Insamlandet av data till databasen bidrar till att bevara ett unikt svenskt kulturarv åt eftervärlden och gynnar därmed en hållbar utveckling. Informationen i databasen kan hjälpa antikvarier att fatta beslut med ekonomiska konsekvenser, då den kan tillhandahålla underlag för att bedöma behovet och värdet av åtgärder. Databasen bidrar också till dokumentation och inventering av delar av orglar som är unika och skyddade av fornminneslagen.
GoArt databas
Keywords: culture; kultur; church; kyrka; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; HISTORY; HISTORIA; History; Historia; Musicology; Musikvetenskap